Notch regulation of tumor angiogenesis. (April 2011) - Bridges, Esther; Oon, Chern Ein; Harris, Adrian
The growth of new blood vessels (angiogenesis) is critical for tumor growth and progression. The highly conserved Notch signaling pathway is involved in a variety of cell fate decisions and regulates many cellular biological processes, including angiogenesis. Aberrant Notch signaling has also been implicated in tumorigenesis. Notch ligands and receptors are expressed on many different cell types present within the tumor, including tumor cells and the stromal compartment. This article highlights in particular the various mechanisms by which Notch signaling can mediate tumor angiogenesis. The most studied Notch ligands, Delta-like 4 and Jagged1, competitively regulate tumor angiogenesis. Studies have demonstrated that Delta-like 4 functions as a negative regulator of tumor angiogenesis, whereas Jagged1 promotes angiogenesis. Understanding the implications of Notch signaling in various tumor backgrounds will enable the effects of specific Notch signaling inhibition on tumor angiogenesis and growth to be evaluated as a potential for a novel antiangiogenic therapy in the clinic.